A comparative study between glidescope® videolaryngoscope and direct laryngoscope using modified rapid sequence induction on haemodynamic parameters during intubation - Azarina, Zakaria (2008)
There are different techniques of intubation of trachea apart from standard direct laryngoscopy. Every technique produces sympathetic response in varying degrees. Glidescope® videolaryngoscope, is a relatively new intubating device to improve the glottic view without aligning the three airway axes as done in standard direct laryngoscopy and is said to cause less airway manipulations. Our study is to see if Glidescope® videolaryngoscopic technique would alter the sympathetic response as normally seen in standard laryngoscopy. To assess haemodynamic responses between direct laryngoscopy and Glidescope® videolaryngoscope during laryngoscopy and intubation. This is a prospective randomized study involving 64 ASA I and II patients divided into 2 groups (n=32); direct laryngoscopy and Glidescope® group. Anaesthesia was induced with intravenous injection of fentanyl 1.51Jg/kg, propofol 2mg/kg and rocuronium 1 mg/kg. Orotracheal intubation was started at least 1 minute after rocuronium injection. Noninvasive blood pressure (BP), heart rate and oxygen saturation were recorded before (baseline value) and immediately after induction, during intubation, and for 5 minutes later, at one-minute intervals. Intubation time was significantly longer in the Glidescope® group (mean 35.67±9.59sec) when compared to direct laryngoscopy group (mean 20.13±5.03sec), p<0.001. In the Glidescope® group, the systolic blood pressure, diastolic blood pressure, mean arterial pressure and heart rate were significantly higher than the direct laryngoscopy group. The increase in heart rate in Glidescope® group took more than 5 minutes to return to baseline values compared to only 3 minutes in direct laryngoscopy group. Direct laryngoscopy showed better haemodynamic parameters of mean SBP, DBP, MAP and heart rate compared to Glidescope® videolaryngoscope. However, the increase in haemodynamic parameters in the Glidescope® group was not more than 20% of baseline values and this was still acceptable to our routine standard anaesthetic management.